Distrofia miotônica: aspectos clínico-laboratoriais em 19 casos Myotonic dystrophy: some clinical and laboratorial data in 19 cases - Milberto Scaff; Ana Maria C. Tsanaclis; José Antonio Levy (Arquivos de Neuro-Psiquiatria)
São relatados os casos de 19 pacientes com distrofia miotônica. São discutidos alguns aspectos clínicos e para-clínicos da doença: eletroforese e imunoeletroforese de proteínas do sôro, eletrocardiograma, eletrencefalograma, radiografia de crânio e pneumencefalograma. Os resultados apresentados foram comparados àqueles da literatura. Some clinical and laboratorial data in 19 patients with myotonic dystrophy are reported. The results of electrophoresis of serum proteins, X-ray of skull, pneumoencephalogramm and electromyogramm are similar to those reported by other authors. Electrocardiographic studies disclosed: left or right anterior hemiblock in 37,50% of the patients; rythm disturbances in 12,50%, and other alterations included supra-ventricular extrassystoles, right branck block and disturbances in intra-ventricular conduction. The results of serum protein immuno-elecrophoresis were as follows: IgA — normal in 61,25%, increased in 18,75% and decreased in 12,50%; IgM — normal in 43,75%, increased in 37,50% and decreased in 18,75%; IgG — normal in 31,25%, increased in 25% and decreased in 43,75%. Abnormalities of immunoglobulins were found to be mainly in IgG fractions, but also in IgA and IgM. Although IgC was significantly decreased in our patients we found other abnormalities of immunoglobulins with no definite pattern.